Adalimumab medium‐term dosing strategy in moderate‐to‐severe hidradenitis suppurativa: integrated results from the phase III randomized placebo‐controlled PIONEER trials. (14th August 2019) - Jemec, G.B.E.; Okun, M.M.; Forman, S.B.; Gulliver, W.P.F.; Prens, E.P.; Mrowietz, U.; Armstrong, A.W.; Geng, Z.; Gu, Y.; Williams, D.A.; Teixeira, H.D.; Kimball, A.B.
Summary: Background: Weekly adalimumab (Humira ® ) is approved for the treatment of hidradenitis suppurativa (HS) based on the 12‐week placebo‐controlled periods of the two phase III PIONEER trials. Objectives: Using PIONEER integrated trial results, we aimed to evaluate the optimal medium‐term adalimumab maintenance dosing strategy for moderate‐to‐severe HS. Methods: Each trial had two double‐blind periods; 12‐week Period A and 24‐week Period B. Patients randomized to adalimumab 40 mg every week (ADAew) (Period A), were rerandomized in Period B to ADAew (ADAew/ew), ADA every other week (ADAew/eow), or placebo (ADAew/pbo). Placebo‐randomized patients were reassigned in Period B to ADAew (PIONEER I) or placebo (PIONEER II). The primary outcome was HS Clinical Response (HiSCR). Patients who lost response during Period B were discontinued from the study and offered an option to enter the open‐label extension (OLE) to receive ADAew. Results are reported across the two study periods, and data were combined from the two study periods and the OLE. Results: For week‐12 HiSCR achievers, the HiSCR week‐36 rate was 48·1% (ADAew/ew) vs. 46·2% (ADAew/eow) and 32·1% (ADAew/pbo). Combining (post hoc) these patients with week‐12 partial responders further differentiated outcomes in Period B (ADAew/ew 55·7% vs. ADAew/eow 40·0% and ADAew/pbo 30·1%). Period‐B adverse‐event rates were ADAew/ew 59·6% vs. ADAew/eow 57·4% and ADAew/pbo 65·0%. One patient (ADAew/ew) reported a serious infection. Conclusions: Weekly adalimumab treatment, effective throughout 36 weeks, was the optimal maintenance medium‐term dosing regimen for this population. At least partial response after 12 weeks with continued weekly dosing had better outcomes than dose reduction or interruption. Patients who do not show at least a partial response to weekly adalimumab by week 12 are unlikely to benefit from continued therapy. No new safety risks were identified. What's already known about this topic? Hidradenitis suppurativa (HS) is a chronic inflammatory disease, commonly misinterpreted as an infection and treated with long‐term antibiotic regimens or surgical incisions. Based on the chronicity of HS and the lack of evidence for efficacious and safe long‐term HS treatments, it is important to evaluate medium‐ to long‐term therapies for HS. Weekly adalimumab (Humira ® ) is approved for the treatment of moderate‐to‐severe HS based on the two phase III PIONEER trials. What does this study add? This study pooled data from the two PIONEER trials, providing a more robust assessment of outcomes. After at least partial treatment success with weekly adalimumab short‐term therapy (12 weeks), continuing weekly dosing during the subsequent 24 weeks had better outcomes than dose reduction or treatment interruption. Patients who do not show at least a partial response to weekly adalimumab by week 12 are unlikely to benefit from continued therapy. Abstract : Linked Comment:  Micheletti. Br J Dermatol 2019; 181 :886–887 . Respond to this article